Non-Stoichiometric Titanium-Oxide Gate Electrodes for EGFET Based pH Sensors - Zsombor Szomor; Lilia Bató; Silvia Stágl; Orsolya Hakkel; Attila Sulyok; Csaba Dücső; Zsófia Baji; Péter Fürjes (Proceedings, 2024)
A compact pH measuring electrochemical sensor module was developed for Smart Multi-Well Plates (SMWP) applicable for highly parallelized cell culture analysis using incorporated Organ-on-Chip devices. A specific electronic architecture was designed and manufactured containing an extended gate field effect transistor as the transducer device. Electrochemical electrodes were functionalized using pH sensitive metal-oxides and applied as the gate material. The composition and the related pH sensitivity of differently deposited materials were characterized and the suitability of ALD-deposited, non-stoichiometric titanium oxide (TiOx) for sensitive pH measurement was verified showing excellent responses close to the ideal Nernstian slope (59 mV/pH).